2022
DOI: 10.3389/fvets.2022.939440
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in porcine miR-22 is associated with pork color

Abstract: MicroRNAs (miRNAs) are posttranscriptional regulators that play key roles in meat color regulation. Changes in miRNA expression affect their target mRNAs, leading to multifunctional effects on biological processes and phenotypes. In this study, a G > A mutation site located upstream of the precursor miR-22 sequence in Suhuai pigs was significantly correlated with the meat color parameter a*(redness) of the porcine longissimus dorsi (LD) muscle. AA genotype individuals had the highest average meat color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In domestic animals, some miRNA variants are associated with economically important traits. For example, g.17104G > A of miR-208b is associated with the proportions of type I and IIb fibre numbers and drip loss in Berkshire, Landrace, and Yorkshire pigs [ 51 ], a G > A variant of miR-22 is related to meat colour parameters in Suhuai pigs [ 52 ], g.–113C > A of miR-9 is related to litter size in Markhoz goats [ 53 ], and g.–13G > A and g.–24T > G of miR-27a-3p are associated with litter size in Hu sheep [ 54 ]. In the present study, we identified a novel variant (g.–703indelT) of miR-423, an inhibitor of sow GC apoptosis, that is markedly associated with the NSB trait.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic animals, some miRNA variants are associated with economically important traits. For example, g.17104G > A of miR-208b is associated with the proportions of type I and IIb fibre numbers and drip loss in Berkshire, Landrace, and Yorkshire pigs [ 51 ], a G > A variant of miR-22 is related to meat colour parameters in Suhuai pigs [ 52 ], g.–113C > A of miR-9 is related to litter size in Markhoz goats [ 53 ], and g.–13G > A and g.–24T > G of miR-27a-3p are associated with litter size in Hu sheep [ 54 ]. In the present study, we identified a novel variant (g.–703indelT) of miR-423, an inhibitor of sow GC apoptosis, that is markedly associated with the NSB trait.…”
Section: Discussionmentioning
confidence: 99%